Pemberdayaan Usaha Mikro dan Kecil Untuk Peningkatan Ekonomi Desa Talang Pauh Bengkulu Tengah - Bertha Iin Esti Indraswanti; Sunoto Sunoto; Antoni Sitorus (UNIB Press, 2024)
Micro and Small Enterprises (MSEs) have an important role in poverty reduction. Although, there are many problems in the process of developing a business. Rural businesses have various limitations. It often based on their mindset regarding conventional business management. Open minded can be a trigger creativity and innovation. Sometimes, external encouragement is needed. MSEs empowering need collaboration of government, collage and other community. Talang Pauh is one of villages in Pondok Kelapa subdistrict of Bengkulu Tengah which has some MSEs with many limitations. The village potential based business development and market orientation according to MSEs competence. The goals of community service were to increase knowledge and insight of MSEs businesses, to motivate community to utilize their resources, to help MSEs businessman in making business plans. The method of community activities service was dialog and counseling. MSEs empowering is needed to strengthening the village economy. The first step is to increase knowledge and insight of MSEs businesses from several aspects: small business management, human resource management, marketing strategy. The second step is empowering. It can do by activities: enabling, empowering and protecting. The success of empowering is determined by participation of various parties.